High thermoelectric performance of p-type Fe2V0.8Mn0.2Al Heusler alloy thin films grown on insulating oxide substrates - Rajveer Jha; Naohito Tsujii; Alexander Riss; Michael Parzer; Ernst Bauer; Takahiro Baba; Takao Mori (Science and Technology of Advanced Materials)
High-performance thermoelectric (TE) materials near room temperature are crucial for cooling and energy harvesting applications. This study reports the outstanding thermoelectric performance of p-type Mn-doped Fe2VAl Heusler alloy thin films, specifically Fe2V0.8Mn0.2Al, prepared using magnetron sputtering. These films were deposited on insulating oxide substrates to eliminate any spurious contributions from the substrate. Large p-type Seebeck coefficients (S) have been observed for all films, revealing a maximum power factor of 4.26 mWK−2m−1 at 300 K. This study revealed thickness-dependent thermoelectric properties, with the highest power factor achieved in the 500 nm film. Films with d = 300 nm and 500 nm exhibit weak ferromagnetism. Hall resistivity measurements evidence an anomalous Hall effect (AHE) for the 300 nm and 500 nm samples. The AHE is strongest for the 500 nm film, consistent with a magnetic enhancement of the Seebeck coefficient and power factor. Additionally, we synthesized Al-rich p-type Fe2V0.9Mn0.1Al1.5 thin films at room temperature, 200°C, 400°C, and 600°C. The film deposited at 600°C exhibits an exceptional figure of merit ZTappr ~0.8 and a power factor of 6.7 mW·K−2·m−1 at room temperature, which are respectively, 4 times and 1.5 times larger than the best values ever reported for any bulk or thin film p-type Fe2VAl-based material.